Implementasi Aplikasi E-Reporting Infrastructure (ERI) Sebagai Media Monitoring Pengaduan Kerusakan Fasilitas Kampus - Usman Nurhasan; Rakhmat Arianto; Candra Bella Vista; Embriani Dewi Lestari; Mita Kartina Sari (PETIR, 2022)
The quality of educational facilities and infrastructure is a measure of the success of the teaching and learning process. Over time, these facilities and infrastructure will suffer damage and their quality will decline. Reports of damage to facilities and infrastructure are always made verbally. Another issue that arises is that Sarpras officers have not seen photographic evidence of the reported condition of the infrastructure. This problem can make it difficult for Sarpras agents to identify infrastructure. The reporting party often does not obtain information about the status of the response from the report. This issue is caused by the fact that no media can be used by the reporter to know the status of the reporting of user complaints. To minimize the reporting of damage errors, an information system can be applied. The application that can be applied in the problem of reporting damage to campus infrastructure is E-Reporting Infrastructure (ERI). This application aims to provide access for registrants and stakeholders to monitor each other's damage reports so that the priority scale for processing recommendations is immediately determined. The recommendations must be able to adapt to the variables which are the needs and priorities of management. The process of determining recommendations will be more stable if it is processed by an algorithm integrated into the ERI. The algorithm that will be applied is a practical and multi-criteria ranking algorithm, including Topsis and SAW. The computation results obtained will be compared in order to determine the efficiency and characteristics of the algorithm.